Hematopoietic Stem Cell Transplantation for Primary Immunodeficiencies - Gennery, Andrew R.; Albert, Michael H.; Slatter, Mary A.; Lankester, Arjan (Frontiers in Pediatrics, 2019)
The field of primary immunodeficiencies has pioneered the way in many of the advances in haematopoietic stem cell transplantation and cellular therapies over the last 50 years. In 1968, three patients with primary immunodeficiencies – one with Wiskott Aldrich syndrome and two with X-linked severe combined immunodeficiencies – were the first patients to demonstrate sustained benefit and prolonged cure from the primary genetic defect following allogeneic haematopoietic stem cell transplantation. The story of our specialty, whilst at the inception of haematopoietic stem cell transplantation, is thus short – in answer to the question “what is the long term outcome of patients transplanted for primary immunodeficiencies?”, we often have to say that we do not really know. We believe, in many cases, that patients who undergo haematopoietic stem cell transplantation for primary immunodeficiencies will live a normal lifespan with a fully corrected immune system. However, it is only now that we are beginning to dissect long term outcomes and the relationship to the underlying genetic defect, age and pre-morbid condition of the patient at time of transplantation, stem cell source and donor, effect of pre-transplant cytoreductive chemotherapy conditioning. The long term consequences of post-transplant complications such as graft versus host disease, veno-occlusive disease or immune dysregulation are also being recognised. Additionally, some genetic defects have a systemic distribution, and we are learning the natural history of these defects once the immunodeficiency has been removed.